2009
DOI: 10.1159/000218180
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Interleukin-6 in the Development of Norepinephrine-induced Left Ventricular Remodeling in Mice

Abstract: Background: Elevated serum concentration of interleukin (IL)-6 is a predictor for poor prognosis in congestive heart failure. It was shown previously in rats, that IL-6 expression in the left ventricle (LV) was followed by LV hypertrophy. Methods: Using IL-6 deficient mice (IL-6-/-), we studied the role of IL-6 in a model of norepinephrine (NE)-induced LV hypertrophy. Results: In wild type (WT) mice, IL-6 mRNA expression and its concentration in the serum were elevated after 4 h of NE-treatment (s.c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…7A). In addition, norepinephrine failed to initiate hypertrophy in IL-6 KO mice (Meier et al, 2009) and IL-6 failed to initiate a hypertrophic response in a 1A/B KO mice (Fig. 7C), suggesting that IL-6 is a prominent factor in a 1 -AR-mediated cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
“…7A). In addition, norepinephrine failed to initiate hypertrophy in IL-6 KO mice (Meier et al, 2009) and IL-6 failed to initiate a hypertrophic response in a 1A/B KO mice (Fig. 7C), suggesting that IL-6 is a prominent factor in a 1 -AR-mediated cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, it has been reported that the serum concentration of IL-6 increases after myocardial infarction, congestive heart failure, and hypertrophic and dilated cardiomyopathy (14). IL-6 can promote myocyte hypertrophy and induce norepinephrine-mediated LV remodeling (32). IL-6/gp130-mediated signaling is involved in overload-induced cardiac hypertrophy in the rodent heart (35).…”
Section: Discussionmentioning
confidence: 99%
“…Among other inflammatory cytokines that have been studied in animals is IL-6, which has been shown to induce negative inotropic effects (82,83,84) as well as hypertrophy, fibrosis, and diastolic dysfunction (85). IL-1β is a cytokine in the IL-1 family that has gained growing attention as previous clinical studies have shown a significant beneficial effect by inhibiting IL-1β (55,86,87).…”
Section: Pathogenic Role Of Local and Systemic Inflammation In Hfmentioning
confidence: 99%